Climate, not grazing, influences soil microbial diversity through changes in vegetation and abiotic factors on geographical patterns in the Eurasian steppe - Qiqige, Bademu; Wei, Bin; Wei, Yuqi; Liu, Mohan; Bi, Yixian; Xu, Ruixuan; Liu, Nan; Yang, Gaowen; Zhang, Yingjun (Frontiers in Plant Science, 2023)
Livestock grazing has a significant impact on the biodiversity of nature grassland ecosystems, which is mainly regulated by climate factors. Soil microbes are essential components of biogeochemical cycles. However, the coupling effects of grazing with MAT (mean annual temperature) and MAP (mean annual precipitation) on soil microbial communities remain inconsistent. Our study considered the various climates in four grasslands as natural temperature and precipitation gradients combined with grazing intensity (GI). We collected and analyzed vegetation and soil physiochemical properties from four grasslands. Our results showed that climate factors (CF) changed β diversity of soil bacteria and fungi while grazing intensity and their interaction merely affected fungi β diversity. Furthermore, climate factors and grazing intensity impacted changes in vegetation and soil physiochemical properties, with their interaction leading to changes in EC and MBC. Our analysis revealed that climate factors contributed 13.1% to bacteria community variation while grazing intensity contributed 3.01% to fungi community variation. Piecewise SEM analysis demonstrated that MAT and MAP were essential predictors of bacteria β diversity, which was significantly affected by vegetation and soil carbon and nitrogen. At the same time, MAP was an essential factor of fungi β diversity and was mainly affected by soil nitrogen. Our study indicated that bacteria and fungi β diversity was affected by different environmental processes and can adapt to specific grazing intensities over time.